Fracionamento do nitrogênio e dos carboidratos de plantas encontradas na caatinga no Rio Grande do Norte - Cabral, João Eudes Soares (Universidade Federal Rural do Semi-Árido, 2014)
In order to meet the forage potential of foods from chemical analysis and fractionation of nitrogen and carbohydrate portions, 12 species that have demonstrated good potential forage were collected: grasses, Buffel grass (Cenchrus ciliaris) and Tanzania grass (Panicum maximun); legumes, Catingueira (bracteosa Caesalpinia), Jurema Preta (Mimosa hostilis, benth) and Leucaena (Leucaena spp.), all trees; and other herbaceous plants extract: Erva de Santa Luzia (Commelina erecta L.), Fato de Piaba (Richardia grandiflora), Jitirana (aegyptia Merremia), Jitirana Roxa (Ipomoea bahiensis, willd), Salsa-de-Praia (Ipomoea brasiliensis) , Favela (Cnidoscolus phyllacanthus) and Pau Branco (Auxemma oncocalyx). Conventional analyzes: dry matter (DM), crude protein (CP) ether extract (EE) and ash were carried out according to AOAC (1990). For neutral detergent fiber (NDF), acid detergent fiber (ADF) cellulose (CEL), hemicellulose (HEM) and lignin (LIG), adopted the methodology proposed by Van Soest et al. (1991). The nitrogen component, according to CNPCS, was divided into fractions A, B1, B2, B3 and C. Since carbohydrates were divided into fractions A + B1, B2 and C. Are observed in the results obtained, there was variation in ether extract (EE) of 1.3% to 6.1% of dry matter (DM%) for Tanzania grass and Leucaena, respectively. As for the Crude Protein (CP), the changes observed were 7.1% to 20.2% for the Buffel grass and Leucaena, also respectively. The variation of the neutral detergent fiber (NDF) was observed from 20.0% to 71.7% for the grass Favela and Tanzania, respectively. The values found for neutral detergent fiber (ADF) were 14.3% and 44.4% for Favela Grass and Tanzania, respectively. In the case of lignin (LIG), the variations were 3.8% for Jurema Preta and Pau Brancoto 9.4% for Catingueira. For the fractionation of carbohydrates, and the Catingueira Fato Piaba showed greater proportions of fraction C (11.8% and 12.0%, respectively). The Grass and Buffel grass Tanzania showed the highest values for fraction B2, with 74.4% and 78.7%, respectively. The Catingueira and Salsa-the-Beach had the highest values for the portion of A + B1, with 48.4% and 50.6%, respectively. On fractionation of the nitrogenous portions, the species showed values ranging from 14.1% to 44.5% for Tanzania grass and Buffel Grass, respectively, for the fraction A (NNP). The Fato de Piaba and Leucaena species showed the highest values being 38.4% and 40.0% respectively for the fraction B1. The Grass and Buffel grass Tanzania were the species that showed the highest values for fraction B2, with 74.4% and 78.7%, respectively. In B3 fraction, the variation was 1.3% to 5.8% for the apparel and Piaba Catingueira respectively. The portions of the nitrogen fraction C showed the highest values in the plant Fato de Piaba and Pau Branco (6.5% and 5.2%), respectively
Chemical analysis-bromatological and fractioning of carbs and nitrogen fraction of plants found in caatinga Rio Grande do Norte.
Keywords: Alimentos; Caatinga; CNPCS; Potencial forrageiro; Produção animal; Semiárido; Foods; Caatinga; CNPCS; Forage potential; Animal production; Semiarid; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL